DETEKSI KEBOCORAN PADA TABUNG GAS LPG MENGGUNAKAN SENSOR MQ-5 BERBASIS ANDROID - Kahar Muzakkar; Faisal; A. Muhammad Syafar (AGENTS: Journal of Artificial Intelligence and Data Science, 2021)
[LEAK DETECTION IN LPG GAS CYLINDER USING ANDROID-BASED MQ-5 SENSOR] In this study there had been designed the LPG gas cylinder leak detector using Microcontrollers and MQ5-based MQ5 sensors. The purpose of this study is to make a series of MQ5 sensors to detect LPG gas levels which then give notifications in mobile applications and provide handling through mobile applications and handling automatically if a gas leak occurs. When NodeMCU ESP8266 leaks receive information on a gas leak from the MQ-5 sensor, it will immediately provide instructions to the buzzer to ring alarm as a warning of the surrounding person, and give information in the form of a notification in the mobile application that there is a gas leak then gives an order to revoke the regulator through mobile application. Automation carried out has different treatments in accordance with the range of gas levels detected. The range of gas levels is PPM <500, 500 <ppm <1000 and ppm> 1000. The sensor circuit that has been made can detect gas content by up to 33000 ppm. The results of testing on the LPG gas leakage automation system, namely the system can work when there is a leak in LPG gas and effectively to reduce LPG gas levels to the safe zone. Keywords: Microcontroller, NodeMCU ESP8266, MQ5 Sensor, Servo Motor, Buzzer, and Blynk